Safety Concern and Regulatory Status of Chemicals Used in Cosmetics and Personal Care Products - Manthan Kaushik; Uzma Farooq; Mohd Shoab Ali; Mohammad Javed Ansari; Zeenat Iqbal; Mohd Aamir Mirza (MDPI AG, 2023)
Cosmetics and personal care products (PCPs) are a few of the most commonly used products across the globe with a whopping market share of approximately USD 500 billion. These products are used for cleansing purposes and for improving the quality and beauty of the face, hair, and skin. There are many chemical substances involved in the manufacturing of cosmetics and PCPs. These chemical substances incorporated in cosmetics or PCPs are crucial to develop high-quality products with superior appearance, applicability, and stability; however, excessive use of such chemicals in cosmetics and PCPs has become a safety concern as many of these are reported to cause severe health complications. Overuse of cosmetics and PCPs with hazardous material should be minimized, especially by pregnant women and children. Gynecologists advise pregnant women not to use cosmetics and PCPs with hazardous chemicals. The implementation of a lawful framework is crucial to establish the safety of cosmetics and PCPs. Cosmetic companies/industries must be strictly regulated and made compliant to the guidelines in order to protect human health and minimize safety concerns. In this review, hazardous chemicals incorporated in the personal care products/cosmetics and their related risk and health complications have been discussed in detail. Additionally, regulatory status and clinical trials of chemical substances that involve toxicity and causing severe complications have also been discussed.